Intertwining Narrative and Technology: Reinterpreting European Cultural Heritage through the Voices of Latin American Women Writers. - Comino, Alba (International Journal of Humanities & Arts Computing: A Journal of Digital Humanities, 2024)
Travel literature not only provides relevant information about cultural heritage, such as authorship, chronology or location, but also reveals the impressions evoked by its reception. This article describes the methodology of the ongoing REWIND project, which explores European cultural heritage through the perspectives of Latin American women writers who travelled to Europe in the early twentieth century. The project seeks to amplify the voices of non-European women committed to feminism and sociocultural diversity to foster decolonial, inclusive and pluralistic historical narratives. On the one hand, we address the configuration of the project corpus, the semantic annotation process, and the design of the ontological modelling according to the deep data concept. On the other hand, we explain the analysis of the relationships between cultural heritage, time, space and emotion. The project uses travel literature in digital format to retrieve, study and interpret data on cultural heritage, creating a workflow that integrates information from various historical sources to raise further questions and provide new insights. The proposed methodology follows the FAIR principles and prioritizes using open-source software to ensure reproducibility and facilitate the use of deliverables in other studies.